Architect Vladimir Lojanica - Milašinović Marić, Dijana (Arhitektura i urbanizam, 2023)
Gallery of the Faculty of Fine Arts, June 2023. Exhibition on the occasion of the Grand Prize in Architecture, awarded by the Association of Architects of Serbia for lifetime achievement.